Rapid response team in the intensive care and inpatient units of a large hospital in Belo Horizonte, MG, Brazil: an observational study (Brazilian Journal of Health Research, 2023)
Introduction:The rapid response team (RRT) is a system intended for the care of patients in aggravating circumstances outside a more complex and specialized environment to meet urgent situations. Objectives: To analyze the attendance data of a rapid response team of a large philanthropic hospital in Belo Horizonte-MG. Methods: This is a retrospective, observational and descriptive study that was carried out through the analysis of care data and monitoring of a Quick Response Team of a large philanthropic hospital, with more than a thousand beds 100% Unified Health System, in Belo Horizonte-MG, between January 2017 and June 2018. Results: The results of this work showed that during the study period there were 1,942 code yellow calls. The activities developed by RRT professionals were: guidelines, being more frequent in relation to diagnostic investigation, respiratory support, hemodynamic monitoring; the performance of procedures, mainly orotracheal intubation and therapies such as volume replacement with crystalloid solutions, use of vasoactive drugs, antimicrobials, analgesics, oxygen and sedatives. Conclusion: This work demonstrates the activities of a rapid response team within a hospital, its importance in numbers, as well as the epidemiological criteria of patients treated by this team. In addition, it allows for a discussion on better communication/standardization and implementation of protocols in order to benefit greater professional autonomy for nurses, as well as to act quickly in an adversity.
Keywords: Hospital rapid response team; Clinical deterioration; Patient safety